A Learning Ecology Approach in a General Chemistry Course: Identifying Self-Regulated Learning Strategies among Students - Carazo Mesén, Jenncy (2025)
A virtual learning ecology was implemented in the General Chemistry course offered at the Interuniversity Campus of Alajuela, University of Costa Rica, during the first semester of 2023. The objective was to investigate the presence of self-regulated learning strategies among students engaged with this learning ecology. This ecology consisted of digital resources and tools developed through ICT to support course content. The study employed a mixed-methods approach, using a nested concurrent design with a dominant model (DIAC). Sixty students enrolled in the course participated in the quantitative phase, while 12 students took part in the qualitative phase, all from the Industrial and Mechanical Engineering programs. Quantitative data were collected through a questionnaire, and qualitative insights were gathered using a focus group. Results indicated that motivation is the primary driver of self-regulated learning, serving as the foundational factor for initiating, persisting, and achieving learning goals. Additionally, planning and control strategies emerged as essential components for effective learning management, enabling deeper processing of information, comprehension of complex concepts, and adaptation to academic challenges. This learning ecology facilitated interactions with diverse elements, including technology, digital resources, and social exchanges with peers and instructors. The findings suggest that promoting such spaces in university courses can enhance students' ability to self-regulate their learning effectively. It is recommended that instructors develop and integrate learning ecologies as these environments offer flexibility and improved access to educational resources, enriching the overall educational experience.